PUBLIC-PRIVATE PARTNERSHIP COMPONENTS IN THE EUROPEAN UNION COUNTRIES (Innovative professional education, 2024)
The components of public-private partnership in the European Union are motives, management, structure, and the mechanism of partnership. It has been established that the motives for creating alliances are different for the private sector and the public sector. Public-private partnership is characterised by a shift in emphasis from hierarchical to network management. Accordingly, management consists of self-organisational and inter-organisational networks. It is determined that the basis of the partnership mechanism is the legitimacy of the alliance and building trust between partners.
Keywords: public-private partnership (PPP), components of PPP, principles of partnership management, legitimacy of partnership, building trust of partners